Association of diastolic and systolic blood pressure with depression: a cross-sectional study from NHANES 2005-2018 - Zhang, Huifeng; Xu, Ying; Xu, Yaying (Frontiers in Psychiatry, 2024)
Many studies worldwide have reported the association between mental health and blood pressure, but the results are mixed, and even contradictory. We aim to investigate the relationship between systolic and diastolic blood pressure and depression in the entire US population.This study analyzed cross-sectional data from the National Health and Nutrition Examination Survey (NHANES) from 2005 to 2018. All adults completed 3-4 blood pressure measurements after sitting quietly for 5 minutes. Depression was diagnosed